Functional MRI imaging in localizing motor paradigm - Tavares, Óscar (2014)
Objectives – Understanding how the brain works were the neuroscience’s goal, since day one. The cerebral analysis developments came along with the widespread of fMRI usage. Following the neuroscience facts, this study aims to identify the cerebral localization of the motor cortex, in a young and healthy population. By allowing a better knowledge of this area, it gives an important contribution to neurology science. Material and methods – fMRIs were performed on 30 healthy subjects, in clinical medical imaging. To achieve this purpose, we employed proper resonance equipment. The motor paradigm used was the fingers’ movement. By the obtained images, the region’s areas were measured.  The data were analysed by a statistic program (SPSS version 19). Conclusion – In conclusion, we observed that the area which was more active, when motor paradigms were in execution, relies on the left cerebral hemisphere.